2014
DOI: 10.3390/ijerph110504729
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health and Life Experiences of Pregnant Adolescent Mothers in Jamaica

Abstract: A recent Jamaican school-based survey revealed that 23.1% of 13–15 year-olds, had attempted suicide one or more times during the last 12 months. Research that links adolescent pregnancy and suicidal behaviour is lacking in Jamaica. Psychological distress and suicidal behaviours amongst pregnant adolescents elsewhere in the Americas has been documented at prevalence of between 13.3%–20%. The purpose of the study was to explore the experiences and the impact of pregnancy on pregnant adolescent psychological heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
4
28
1
6
Order By: Relevance
“…There are several detrimental health, psychosocial, and economic consequences connected with AP that are disturbing and should not be underestimated (18)(19)(20)(21). Research till date has proven that pregnant females younger than 17 years have a higher incidence of health complications related to mother and child compared to grown-up women, though these complications may be more severe among youngest adolescents (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…There are several detrimental health, psychosocial, and economic consequences connected with AP that are disturbing and should not be underestimated (18)(19)(20)(21). Research till date has proven that pregnant females younger than 17 years have a higher incidence of health complications related to mother and child compared to grown-up women, though these complications may be more severe among youngest adolescents (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…In one study 81,1% lived with their partner (married/ cohabiting). 18 For his part, Wilson-Mitchell 19 observed that 60% of pregnant teenagers had a partner at the time of the study and only 28,6% did not maintain their relationship after pregnancy. This can be interpreted as a positive indicator, because pregnancy in adolescence is a serious social and medical problem, which should not only be approached from the obstetric field.…”
Section: Discussionmentioning
confidence: 99%
“…Participants: Pregnant adolescents between 10 to 19 years old, with more than ten weeks of amenorrhea and a confirmed diagnosis of pregnancy who went to outpatient antenatal care offices in Cartagena, Colombia. They were approached by the Children below 16 should give almost all their earnings to their parent 40 (8,0) [5,9-10,8] 81 (16,2) [13,2-19,8] 71 (14,2) [ 11,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]7] 102 (20,5) [17,0-24,3] 185 (37,1) [32,9- [48,0-57,0] 64 (12,9) [10,1- 16,2] A person should always be expected to defend his family against outsiders even at the expense of his own personal safety (22,9) [ 19,8] The members of a family should be expected to hold the same ideas…”
Section: Methodsmentioning
confidence: 99%
“…In addition to pregnancy-related problems such as anemia, premature birth, intrauterine development retardation, premature membrane rupture, early and late baby death 1 , fetal distress, and unsuccessful induction of labor, increases are also observed in psychological problems such as feelings of anxiety, depression and suicidal ideation. 7,11,12,14 These factors all together mean that adolescent pregnancies are a significant health problem.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mental and physical health are known to be affected in adolescent pregnancies, with one study reporting psychological problems or suicidal ideation in 23% of the subjects and another reporting the serious impact of depression, suicidal ideation or attempted suicide on the health of the baby. 12,13 Pregnancy in adolescence affects the physical and mental health of both the mother and the baby and presents a major societal problem. The purpose of this study was therefore to assess the sociodemographic characteristics of pregnant adolescents and their anxieties concerning pregnancy.…”
Section: Introductionmentioning
confidence: 99%